Harnessing stories of home in Fort Good Hope, Northwest Territories: Examining the role of housing and planning in advancing Indigenous self-determination - Pugsley, Aimee; Christensen, Julia (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
It is widely recognized that the housing landscape in northern Canada, characterized by chronic housing insecurity, homelessness, and inadequate policy responses, is in a state of crisis. In Fort Good Hope, a Dene First Nation in the Sahtu region of the Northwest Territories, the K'ásho Got’ı̨ne Housing Society is coordinating a community-led strategy to deliver their own housing and home. While their work supports the call for Indigenous self-determination, the systemic barriers that impede their efforts highlight the challenges of realizing self-determination in the current governance system. This paper draws on a series of interviews and archival research to explore how home, housing, and planning can support self-determination in northern and Indigenous communities. We problematize the stories of housing and planning that construct state dependencies and discursively limit possibilities for self-determination, elevating instead the story of home that empowers Fort Good Hope in its self-determination. Ultimately, we demonstrate the power for knowledge and identity production in housing and planning systems, and highlight the importance of challenging the settler colonial ontologies implicated in state-sanctioned approaches to self-determination.